2020
DOI: 10.3389/fpubh.2020.00007
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Iraqi Kurdistan Health Authorities in Post-conflict Recovery: The Development of a Health Monitoring System

Abstract: Background: Iraq has endured several conflicts and socio-political tensions that have disrupted its public health system. Nowadays, because health data are not collected on a routine basis, the country still lacks proper statistics and, consequently, response plans to meet present and future health needs of its population. An international partnership is developing in the Iraqi Kurdistan a Health Monitoring System with the aim of supporting evidence-based health policy decisions. Methods: The pilot phase for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, at present, little is known about the actual implementation plan [16]. The WHO is supporting initiatives in the Eastern Mediterranean region [17] to develop national health information systems so as to improve timely and comprehensive registration of health data [18,19]. Since 2015, WHO has been implementing an Interactive Electronic Reporting System in Jordan [20], trying to integrate an e-health initiative launched in 2000 with the (still to be achieved) goal of connecting public hospitals in the country within three years [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, at present, little is known about the actual implementation plan [16]. The WHO is supporting initiatives in the Eastern Mediterranean region [17] to develop national health information systems so as to improve timely and comprehensive registration of health data [18,19]. Since 2015, WHO has been implementing an Interactive Electronic Reporting System in Jordan [20], trying to integrate an e-health initiative launched in 2000 with the (still to be achieved) goal of connecting public hospitals in the country within three years [21].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this approach, the University of Rome Tor Vergata (Italy) and the KRI Ministry of Health -with the financial support of the Italian Agency for Development and Cooperation-have initiated a cooperation project to establish the first Health Information System in the KRI, aimed at gathering data on health determinants, births, deaths and health service performance. This project was commenced in 2015 through a pilot phase [43] and now includes about 60 health centres and hospitals, which routinely record health data using ICD-10. The Health Information System is starting to provide high-quality data, which are needed for national and sub-national planning, policy implementation and monitoring of health outcomes and services.…”
Section: Discussionmentioning
confidence: 99%
“…A profound monitoring and evaluation system ought to incorporate mixed research approaches (Bamberger, Rao, and Woolcock 2010). All relevant stakeholders' involvement is necessary in determination of indicators to be tracked (Emberti Gialloreti et al 2020, Malone et al 2014, Diallo et al 2003, Guijt 1999. Participatory monitoring and evaluation involves incorporation of all the stakeholders in all stages and processes of the M&E system, and the engagement helps in determination of the way forward and what modifications are needed for better M&E (Izurieta et al 2011, Estrella et al 2000, Guijt 1999, Estrella and Gaventa 1998.…”
Section: Introductionmentioning
confidence: 99%
“…The most challenging issue in monitoring and evaluation of indicators in healthcare is the development of a systematic way of measurement and utilization of indicators for improvement, development of such a system which incorporates variance reporting requires concerted effort and inclusion of each team member (Brown and Nemeth 1998). There are myriad challenges towards the design, development, and implementation of an effective M&E system; such as stakeholder buy-in, knowledge gap, time constraints, logical frameworks, resources available, and the validity of data, sampling techniques, and the indicator measurements (Emberti Gialloreti et al 2020, Anderson et al 2019, Mthethwa and Jili 2016, Cameron 1993. Emberti Gialloreti et al (2020) concluded that multiple stakeholder involvement is necessary for a successful and timely system in collection and monitoring of health information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation